2009
DOI: 10.5694/j.1326-5377.2009.tb02521.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse outcomes of labour in public and private hospitals in Australia: a population‐based descriptive study

Abstract: Objective: Design, setting and participants: A population‐based study of 789 240 term singleton births in public and private hospitals in 2001–2004, using data from the National Perinatal Data Collection. Main outcome measures: Third‐ and fourth‐degree perineal injury, requirement for high level of neonatal resuscitation, Apgar score < 7 at 5 minutes, admission to neonatal intensive care unit or special care nursery, and perinatal death. Results: 31.4% of the term singleton births occurred in private hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
50
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 30 publications
7
50
1
Order By: Relevance
“…In a recent publication we showed that the rate of caesarean section had increased in both the private and public sector in the past decade in low-risk women 9. It has been argued in a previous publication that these high intervention rates in the private sector led to better perinatal outcomes than in the public sector 2. This publication received significant criticism in letters to the editor3 16 17 for several methodological flaws, including most significantly the failure to adjust for low-birth weight, inadequate ascertainment of congenital abnormalities and failure to look at perinatal morbidity.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In a recent publication we showed that the rate of caesarean section had increased in both the private and public sector in the past decade in low-risk women 9. It has been argued in a previous publication that these high intervention rates in the private sector led to better perinatal outcomes than in the public sector 2. This publication received significant criticism in letters to the editor3 16 17 for several methodological flaws, including most significantly the failure to adjust for low-birth weight, inadequate ascertainment of congenital abnormalities and failure to look at perinatal morbidity.…”
Section: Discussionmentioning
confidence: 89%
“…The remaining 71% (n=204 399) of women gave birth in public hospitals in Australia. Women who are privately insured have been reported to have better maternal and perinatal outcomes compared to women who give birth in public hospitals as public patients2; but it has been argued that these women tend to be less socioeconomically disadvantaged and healthier3 and therefore might be expected to have better outcomes. Arguments about the impact of private status on health outcomes are in reality complex.…”
Section: Introductionmentioning
confidence: 99%
“…Public hospitals are known to serve a disproportionately larger share of patients of relatively low socio-economic status [30]. Women giving birth in public hospitals have been found to be younger, a higher proportion are first births, a greater proportion smoke, and more women present with medical conditions such as hypertension and diabetes [31]. The Health Districts of the study region are known to have higher proportions of socio-economic disadvantage and more people with non-English speaking backgrounds than the national average [9].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that publicly insured women are generally less healthy and in more need of health care services than other women [4-12]. This appears to be related to poor outcomes for infants born at term in Australia [13]. Eliminating the demographic differences between publicly insured and privately insured women would therefore seem important in order to investigate whether there are true differences in neonatal outcomes between these groups of women.…”
Section: Introductionmentioning
confidence: 99%